keithgroup/qcjson: v0.3.0 - Alex Maldonado (Zenodo, 2022)
Added Support for xtb optimizations, single-point energies, and molecular dynamics. (xtb) Support for additional functionals. (ORCA) Support for coupled cluster calculations. (ORCA) Track Hartree–Fock type for ab initio methods. (ORCA) A script to combine JSON files recursively. Adds n_electrons to JSON files. (ORCA) Changed Fixed handling of errors in recursive QCJSON creator operations. Fixed including and excluding keywords in paths. More consistent information about frozen core electrons. Also changed 'frozencore' to 'frozen_core'. Parsing errors will not stop qcjson-creator.py if debug is False. UHF spin contamination correctly parsed for DFT methods. (ORCA) Adding missing ωB97M-V and ωB97M-D3BJ functionals. (ORCA) Removed Examples and support for parsing CCSD(T) calculations using ORCA. There is a cclib (v1.7.1) error when parsing these output files.